PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASIONAL PADA INTENSI KELUAR Di PT. Citra Lestari Anugrah - , David Tampubolon ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Purpose â The focus of this research paper is on the effect of job satisfaction and organizational commitment on turnover intention at PT. Citra Lestari Anugrah. Design/methodology â This research design using design relationship (asosiative) with kuantitative approach. The participants were involved of 76 PT. Citra Lestari Anugrah employees from Team Leader to Chief Supervisor level with permanent employment status, using the Job Satisfaction Survey (Spector, 1997), Three-Component Model (TCM) of employee commitment survey revise edition (Meyer and Allen, 2004) and turnover intention questionnaire (Mobley, 1982, in Kismono, 2011). Findings â The results show that there were negative significant effects from job satisfaction and affective commitment organizationalon turnover intention. Furthermore there are no negative significant effects from continuance and normative commitment to the organization on turnover intention. Research limitations/implications âThis research were limited to the use of internal organization participants, common method bias, central tendency errors, and some of the items in the questionnaire which did not pass the realiability test.The results showed that all the variable average categorized score from participant are in the middle score. It recommended higher average categorized score from participant by performing practical recommendation for organization activities to obtain the desired/valued goals. Originality/value â This research examines the effect of job satisfaction and organizational commitment on turnover intention, from the internal of an Outsourcing Company, rather than conducting research from User Company perspective.